Proyecto de alcantarillado sanitario para la comunidad Paniquindra, Parroquia la Esperanza, Cantón Ibarra, Provincia de Imbabura. - Castelo Toapanta, José María (2013)
The scope of the project is to really translate a need for the community   Paniquinda to improve their quality of life, presenting an analysis of socioeconomic data,   topographic, hydrological, geological-geotechnical   obtained from field work such as laboratory and cabinet, to establish the design bases looking for the most economical solution to cover all aspects related to the collection, conduction and treatment of sewage, solving definitively and efficiently the problems of health that the lack of hygienic means entails.